Lipid Profile and Oxidative Stress Markers in Wistar Rats following Oral and Repeated Exposure to Fijk Herbal Mixture. (20th October 2014) - Adeyemi, Oluyomi Stephen; Orekoya, Bukola Temitope
Abstract : This study determined the effect of the oral and repeated administration of Fijk herbal mixture on rat biochemical and morphological parameters. Twenty-four Wistar rats were distributed into four groups of 6. Group A served as control and received oral administration of distilled water daily. The experimental groups B, C, and D were daily and orally exposed to Fijk herbal mixture at 15, 30, and 45 mg/kg, respectively. Treatments lasted for 21 days. The rats were sacrificed under mild diethyl ether anesthesia 24 hr after cessation of treatment. The blood and liver samples were collected and used for the biochemical and morphological analyses. Oral exposure to Fijk caused elevated levels of rat plasma ALT, AST, triglycerides, LDL, and MDA. In contrast, rat plasma HDL, GSH, and ALP levels were lowered by Fijk oral exposure. Also, the herbal remedy caused a dose-dependent elevation in the plasma atherogenic index. The histopathology examinations of rat liver sections revealed inimical cellular alterations caused by repeated exposure to Fijk. Study provides evidence that oral and repeated exposure to Fijk in rats raised the atherogenic index and potentiated oxidative stress as well as hepatic injury.